2019
DOI: 10.3390/ijms20092265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought Stress and Developmental Stages on Microbial Community Structure and Diversity in Peanut Rhizosphere Soil

Abstract: Background: Peanut (Arachis hypogaea L.), an important oilseed and food legume, is widely cultivated in the semi-arid tropics. Drought is the major stress in this region which limits productivity. Microbial communities in the rhizosphere are of special importance to stress tolerance. However, relatively little is known about the relationship between drought and microbial communities in peanuts. Method: In this study, deep sequencing of the V3-V4 region of the 16S rRNA gene was performed to characterize the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 56 publications
5
53
1
1
Order By: Relevance
“…Proteobacteria, Actinobacteria, and Firmicutes were the mutually dominant bacterial phyla of peanuts and the above plants, indicating that they are the most common dominant bacterial phyla in plant spermosphere soils. In our recent data, Proteobacteria and Actinobacteria dominated in rhizosphere soil of peanut, which suggested that Proteobacteria and Actinobacteria are the two most abundant bacteria in the soil around peanut [1]. The biological function of the two phyla in peanut soils needs further research.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Proteobacteria, Actinobacteria, and Firmicutes were the mutually dominant bacterial phyla of peanuts and the above plants, indicating that they are the most common dominant bacterial phyla in plant spermosphere soils. In our recent data, Proteobacteria and Actinobacteria dominated in rhizosphere soil of peanut, which suggested that Proteobacteria and Actinobacteria are the two most abundant bacteria in the soil around peanut [1]. The biological function of the two phyla in peanut soils needs further research.…”
Section: Discussionmentioning
confidence: 89%
“…Over the past decade, various studies have emerged that implicate members of the rhizosphere microbial communities in enhancing plants stress tolerance by activating stress response or providing a buffer zone for plants against stress [54][55][56]. In the previous paper, the defense mechanism in the microbial community of drought-treated peanut rhizosphere soils was significantly higher than that of the controlled soil [1]. Similar to this, the defense mechanism was also predicted as being higher in salt-treated peanut spermosphere soils in this study ( Figure 6A).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations